1993
DOI: 10.1111/j.1365-2265.1993.tb02388.x
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel syndrome and gynaecomastia during growth hormone treatment of elderly men with low circulating IGF‐I concentrations

Abstract: These observations show that when elderly men with low circulating IGF-I concentrations are treated continuously with hGH, elevation of plasma IGF-I above 1.0 units/ml is associated with a substantial frequency of carpal tunnel syndrome or gynaecomastia. It may be that the effects of the hormone in expanding lean body mass and reducing adipose mass can be achieved, and the side-effects avoided, by maintaining the mean IGF-I level in the range 0.5-1.0 units/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1
8

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(50 citation statements)
references
References 32 publications
4
37
1
8
Order By: Relevance
“…ND possibly caused symptomatic fluid retention (oedema and carpal tunnel syndrome, which can be triggered by fluid retention [37]) in 2 subjects, despite both subjects having reasonable dialysis adequacy. The reason for this is unclear, but may be related to these patients’ degree of residual renal function (which was not assessed in the present study).…”
Section: Discussionmentioning
confidence: 99%
“…ND possibly caused symptomatic fluid retention (oedema and carpal tunnel syndrome, which can be triggered by fluid retention [37]) in 2 subjects, despite both subjects having reasonable dialysis adequacy. The reason for this is unclear, but may be related to these patients’ degree of residual renal function (which was not assessed in the present study).…”
Section: Discussionmentioning
confidence: 99%
“…Cessation of IGF-I therapy has resulted in regression in all reported cases (161). Gynecomastia has been reported as a rare occurrence in elderly men (162).…”
Section: Reported Adverse Effects Of Gh Replacementmentioning
confidence: 99%
“…In a group of elderly men that underwent GH replacement therapy for six months, Cohn, Rudman et al reported a side-effect withdrawal rate of 43% compared to 9% in the placebo group. The most common symptoms were carpal tunnel syndrome, gynecomastia, and hyperglycemia [51]. Yarasheski et al reported a similarly high incidence of carpal tunnel syndrome, edema, and arthralgia [52].…”
Section: Possible Adverse Effects Of Gh Use In Patients Without Aghdmentioning
confidence: 94%